If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + -1X)(9 + -1X) = (9 + -1X)(11 + -1X) Multiply (3 + -1X) * (9 + -1X) (3(9 + -1X) + -1X * (9 + -1X)) = (9 + -1X)(11 + -1X) ((9 * 3 + -1X * 3) + -1X * (9 + -1X)) = (9 + -1X)(11 + -1X) ((27 + -3X) + -1X * (9 + -1X)) = (9 + -1X)(11 + -1X) (27 + -3X + (9 * -1X + -1X * -1X)) = (9 + -1X)(11 + -1X) (27 + -3X + (-9X + 1X2)) = (9 + -1X)(11 + -1X) Combine like terms: -3X + -9X = -12X (27 + -12X + 1X2) = (9 + -1X)(11 + -1X) Multiply (9 + -1X) * (11 + -1X) 27 + -12X + 1X2 = (9(11 + -1X) + -1X * (11 + -1X)) 27 + -12X + 1X2 = ((11 * 9 + -1X * 9) + -1X * (11 + -1X)) 27 + -12X + 1X2 = ((99 + -9X) + -1X * (11 + -1X)) 27 + -12X + 1X2 = (99 + -9X + (11 * -1X + -1X * -1X)) 27 + -12X + 1X2 = (99 + -9X + (-11X + 1X2)) Combine like terms: -9X + -11X = -20X 27 + -12X + 1X2 = (99 + -20X + 1X2) Add '-1X2' to each side of the equation. 27 + -12X + 1X2 + -1X2 = 99 + -20X + 1X2 + -1X2 Combine like terms: 1X2 + -1X2 = 0 27 + -12X + 0 = 99 + -20X + 1X2 + -1X2 27 + -12X = 99 + -20X + 1X2 + -1X2 Combine like terms: 1X2 + -1X2 = 0 27 + -12X = 99 + -20X + 0 27 + -12X = 99 + -20X Solving 27 + -12X = 99 + -20X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '20X' to each side of the equation. 27 + -12X + 20X = 99 + -20X + 20X Combine like terms: -12X + 20X = 8X 27 + 8X = 99 + -20X + 20X Combine like terms: -20X + 20X = 0 27 + 8X = 99 + 0 27 + 8X = 99 Add '-27' to each side of the equation. 27 + -27 + 8X = 99 + -27 Combine like terms: 27 + -27 = 0 0 + 8X = 99 + -27 8X = 99 + -27 Combine like terms: 99 + -27 = 72 8X = 72 Divide each side by '8'. X = 9 Simplifying X = 9
| -2+8x+12=4(2x+3) | | 7x-144=2x-9 | | 6x+5=5(x) | | 8(x-1)=3(2x+2) | | x+2=4y | | 3/8x+2-4/5x1+3/10x+3/2 | | 8/15+1/15 | | x+2.8=.7x+4.9 | | k+q=a | | A=K(n+N)forN | | -2-6x=8-6x | | k+q=aforq | | 80=2(lw+hw+hl) | | 840/1575 | | 3(x+6)=5x | | 2x+2=5y+7 | | 9M^2+12M-12=0 | | 6x^3-6x^2-6x=o | | 4x-4=6x-6 | | 1/3x-1/2+5/5x=3 | | 80=2lw+2lh+2wh | | (X+2)(X+3)=(X-4)(X-5) | | 6x+3x=5-4(2x-3) | | (8/2x+2)=(3/x-1) | | 2x+13=-35 | | -x/7=12 | | 94-3x=11-8x | | x=33800/1.04 | | -7/3a=35 | | 93-3x=11-8x | | (9X-2)-(X+3)=(X-5)(X-7) | | 15x^3-42x^2=0 |